Pengembangan Materi Berdebat Berbasis Model Pembelajaran Yurisprudensi Siswa Kelas X SMA - Nahal, Reski; Muh. Taufik; sultan (Perkumpulan Pengelola Jurnal Bahasa dan Sastra Indonesia serta Pengajarannya, 2019)
This study aims to: (1) produce debating teaching materials based on a model of jurisprudence in Wahdah Islamiyah Makassar High School IT; (2) examine the feasibility of debating material teaching materials based on the model of jurisprudence in class X SMA IT Wahdah Islamiyah Makassar. This research was designed with research and development. The design of this study is R2D2 (Recursive, Reflective Design and Development Model). The data in this study are qualitative and quantitative data from the assessment of experts and practitioners. Qualitative data comes from comments, criticisms, and suggestions from expert and practitioner evaluations of teaching materials. Quantitative data is sourced from scores of expert and practitioner evaluations of the components of teaching materials. The data analysis technique of this study is qualitative data analysis and quantitative data analysis. Qualitative data analysis, namely grouping data and concluding data in the form of comments, suggestions, and criticism from experts and practitioners to improve teaching materials and quantitative data analysis that is looking for the average of each indicator of expert judgment and practitioners for product feasibility. Components of the results of the assessment of teaching materials indicate that the component of content eligibility obtained an average of 3.39, the presentation component of 3.53, the language component of 3.47, the graphic component of 3.64, and the implications for developing competency debating 3.83. This research and development resulted in the product of the Arguing Teaching Material Based on a Model of jurisprudence that had been assessed by experts and practitioners. The results of expert and practitioner evaluations of teaching materials indicate that the assessment is in a very feasible category.